2007
DOI: 10.1038/sj.jhh.1002198
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of angiotensinogen and angiotensin-converting enzyme associated with lower extremity arterial disease in the Health, Aging and Body Composition study

Abstract: The role of renin-angiotensin system (RAS) genes on the risk of lower extremity arterial disease (LEAD) in elderly people remains unclear. We assessed the relationship of genetic polymorphisms in RAS: G-6A, T174M and M235T of the angiotensinogen (AGT) gene, and the angiotensin-converting enzyme insertion/deletion (ACE_I/D) variant to the risk of LEAD in the Health, Aging and Body Composition (Health ABC) Study. This analysis included 1228 black and 1306 white men and women whose age ranged between 70 and 79 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…The data document an association between candidate genes in RAS and CAD, AAA, and CVD, 5,6,26 whereas few data are available concerning PAD. 2,7,8,27 Findings from the present study support that the ACE gene and particularly the ACE I/D polymorphism modulates the predisposition to PAD independently of traditional risk factors.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The data document an association between candidate genes in RAS and CAD, AAA, and CVD, 5,6,26 whereas few data are available concerning PAD. 2,7,8,27 Findings from the present study support that the ACE gene and particularly the ACE I/D polymorphism modulates the predisposition to PAD independently of traditional risk factors.…”
Section: Discussionsupporting
confidence: 73%
“…5,6 The few published reports on the relationship between RAS genes and PAD have had conflicting results. 2,7,8 A recent hypothesis is that people carrying susceptibility polymorphisms in RAS genes might exhibit higher angiotensin II levels, which may be crucial in the development of the disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies, among the populations of northern Chinese Han individuals, 64,85 Asians, 39 Europeans, 39 African Americans, 33 and European Americans, 33 have indicated the absence of association of T174M with EH. In addition, other studies, among the Mexicans, 26 black and white participants, 119 Americans in the Delaware Valley Region, 106 Americans, 120 Caucasians, 121 Chinese Han, 122 and Taiwanese, 89 showed no association between this polymorphism and the risk of the non-familial atrial fibrillation, lower extremity arterial disease, decline in renal function post-transplantation, preeclampsia, pseudoxanthoma elasticum, coronary artery disease, and chronic kidney disease in this mutation, respectively. In our study, no association was observed between these two polymorphisms (including A-20C and T174M) and EH among the both Hani and Yi populations.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of RAAS genes could also play a role in arterial stiffness leading to an increased risk of development of lower extremity arterial disease and possibly, other vascular disease. Recently, Li et al 6 estimated the relationship of ACE I/D variant and G-6A, T174M and M235 T polymorphisms of the AGT gene to lower extremity arterial disease in a large population of elderly white and black participants. Apart from significant differences in the distribution of the RAAS genetic variants by ethnicity (consistent with previous reports) a major finding is the interaction between ACE inhibitors and the A-T haplotype of the AGT gene, a gene-drug interaction that reduces the risk of lower extremity arterial disease in the white population.…”
mentioning
confidence: 99%